2023
DOI: 10.1007/s11661-023-07049-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manufacturing Conditions and Al Addition on Inclusion Characteristics in Co-Based Dual-Phase High Entropy Alloy

Abstract: Three Co-based dual-phase high-entropy alloys (HEAs) were produced by different manufacturing conditions: arc-melting with Ar protection (Ar-HEA), vacuum induction melting in Al2O3 crucible (Cr-HEA) and vacuum induction melting with 0.5 at. pct Al (Al-HEA), which resulted in different levels of impurity elements and inclusion characteristics. The inclusions that precipitated in different HEA samples were investigated through an electrolytic extraction process and scanning electron microscopy-energy dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…[29] Since reactive elements are present in most of the castings examined, excluding these inclusions in regular melting procedures is difficult. [30][31][32][33] The reactive element Al, which interacts with N 2 and O 2 more effectively, is believed to produce an inclusion defect in casting. Therefore, it is reasonable that the black precipitates were an inclusion defect.…”
Section: Microstructure Characterization With Different Samplesmentioning
confidence: 99%
“…[29] Since reactive elements are present in most of the castings examined, excluding these inclusions in regular melting procedures is difficult. [30][31][32][33] The reactive element Al, which interacts with N 2 and O 2 more effectively, is believed to produce an inclusion defect in casting. Therefore, it is reasonable that the black precipitates were an inclusion defect.…”
Section: Microstructure Characterization With Different Samplesmentioning
confidence: 99%
“…MnCr 2 O 4 oxide inclusions are commonly found in CrMnFeCoNi alloys [14][15][16][17], and their influence on mechanical properties has been ignored because of their small volume fraction. Yu et al [18] reported that stable MnO-SiO 2 was formed in Si-added CoCrFeMnNi instead of the harmful MnCr 2 O 4 , which greatly enhanced the corrosion resistance of the alloy. Similarly, the stable inclusions can transform from MnCr 2 O 4 inclusions to Mn(Cr,Al) 2 O 4 inclusions and then to pure Al 2 O 3 inclusions with increasing Al content in HEA [19].…”
Section: Introductionmentioning
confidence: 99%